ANALISIS IKLIM KOMUNIKASI PADA PEGAWAI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN KUNINGAN - Aji Muhamad Jaelani; Ririn Risnawati (Fakultas Ilmu Sosial dan Ekonomi, Universitas Respati Yogyakarta, 2021)
ABSTRACTOrganizational communication climate is one thing that really needs to be considered in an organization because after all the organizational communication climate has an influence on the sustainability of an organization, in order to make an organization that is in accordance with what is expected and aspired by the organization and includes members in it. Therefore, the researcher took the title